Teratogenic Toxicity of Ethanol Extract of Mahkota Dewa Fruit Flesh (Phaleria macrocarpa (Scheff.) Boerl) - Julianti, Maelani; Yuandani; Harahap, Urip (Indonesian Journal of Pharmaceutical and Clinical Research, 2022)
Mahkota Dewa is known as one of the medicinal plants in Indonesia. It contains bioactive compounds and potentially has pharmacological activity. This study aimed to determine the possible toxic effects of Mahkota DewaThe ethanol extract of Mahkota Dewa fruit flesh was given to rats. Group I (control 0.5% Na-CMC), groups II, III and IV as a treatment group (Mahkota Dewa at doses of 100, 500 and 1000 mg/kg bw, respectively). Group V as a control satellite (Na-CMC 0, 5%) and group VI as a satellite of the ethanol extract at a dose of 1000 mg/kg bw., Each groups were treated on day 6 to 15 of gestational. On the 19th day getation, the rats were dissected and observed the skeletal malformations. The data were analyzed using one-way ANOVA followed by a post-hoc tukey. The results toxicity showed that no fetuses had external malformations. On fetal skeletal appearance, all skeletal bone preparations were normal. Based on the study, the ethanolic extract of Mahkota Dewa Fruit Flesh did not cause a teratogenic effect on the fetus during the organogenesis period at doses of 100 mg/kg bw, 500 mg/kg bw, and 1000 mg/kg bw Â